Elevated levels of TRAb IgG autoantibodies are not recognized in endometriosis by the current clinical methods - Petersson, Agnes; Roth, Bodil; Becker, Charlotte; Ohlsson, Bodil (Frontiers in Medicine, 2025)
BackgroundEndometriosis can cause gastrointestinal symptoms that sometimes lead to incorrect diagnosis of irritable bowel syndrome (IBS). Receptors of thyroid-stimulating hormone (TSH) are found in the endometrium and are overexpressed in ectopic endometrium. The role of TSH receptors and thyroid hormones in the pathophysiology of endometriosis has therefore been discussed. No biomarker is available for endometriosis diagnosis, but the findings of TSH receptor antibodies (TRAb) have been found by two different methods. The present study aimed to confirm that TRAb IgG levels are elevated in patients with endometriosis compared with IBS and healthy controls.MethodsA total of 121 patients with a diagnosis of endometriosis and two cohorts with 50 IBS patients and 50 healthy controls were recruited for the study. All subjects had to fulfill study questionnaires regarding sociodemographic factors, lifestyle, medical history, and gastrointestinal symptoms. Blood samples were drawn, and TRAb IgG was analyzed in serum samples at the Departments of Clinical Chemistry at Sahlgrenska University Hospital using the BRAHMS TRAK Human assay from Thermo Fisher Scientific and at Skåne University Hospital using the Elecsys Anti-TSHR assay from Roche Diagnostics. Both methods were developed and used clinically to diagnose Graves’ disease with high specificity.ResultsPatients with endometriosis had the highest BMI (p = 0.001) and prevalence of hypothyroidism (p = 0.005). Endometriosis and IBS patients had many gastrointestinal symptoms, in contrast to the healthy controls. There was no significant difference in the number of patients with detectable serum TRAb between endometriosis patients (n = 10, 8.3%) and controls (n = 2, 4%) (p = 0.512) or between endometriosis patients (n = 10, 8.3%) and IBS patients (n = 3, 6%) (p = 0.758) in Gothenburg. Similar results were found when TRAb was analyzed in serum samples in Malmö, with the same prevalence of TRAb in endometriosis patients (n = 4, 4.9%) as in controls (n = 4, 8.0%) (p = 0.710) and IBS patients (n = 4, 8.0%) (p = 0.710).ConclusionThe available tests in clinical routine could not reveal elevated levels of TRAb in the current exploratory study. Thus, TRAb cannot yet be used clinically as a biomarker of endometriosis. Still, other variants of antibody tests may be used in a laboratory experimental setting. The role of TSH receptors and TRAb in the pathophysiology of endometriosis deserves further research.